To solve the equation \( \frac{33}{x} = -3 \), we can start by multiplying both sides by \( x \) (assuming \( x \neq 0 \)):
\[ 33 = -3x \]
Now, divide both sides by -3:
\[ x = \frac{33}{-3} = -11 \]
So, a value of \( x \) that makes the equation true is \( -11 \). Substituting \( -11 \) back into the original equation gives us:
\[ \frac{33}{-11} = -3 \]
This simplifies to:
\[ -3 = -3 \]
So we compute \( x = -11 \) and verify that it turns into \( -3 = -3 \).
Now, to find a value of \( x \) that makes the equation false, we could choose any value other than \( -11 \) or any value that does not satisfy the equation. For example, let's choose \( x = 1 \):
Substituting \( x = 1 \) into the equation gives us:
\[ \frac{33}{1} = -3 \]
This simplifies to:
\[ 33 = -3 \]
This is clearly false.
Thus, a value of \( x \) that makes the equation false is \( 1\), and when substituted into the equation it turns into \( 33 = -3 \).
In summary:
- A value of \( x \) that makes the equation true is -11. It simplifies to -3 = -3.
- A value of \( x \) that makes the equation false is 1. It simplifies to 33 = -3.